Jazyki mira: Semitskie jazyki. Akkadskij jazyk. Severozapadnosemitskie jazyki - Loesov, Sergey V.; Kogan, Leonid E.; Belova, Anna G. (2009)
Languages of the World: The Semitic Languages. Akkadian. Northwest Semitic.